Single-incision trocar-less endoscopic management of giant liver hydatid cyst in children - Acharya, Himanshu (J Minim Access Surg, 2018)
INTRODUCTION: Laparoscopic management of giant hydatid cyst has limitations such as spillage, poor control, difficulties in suctioning the contents through special ports which are not easily available, difficulty in the obliteration of residual cavity and recurrence. We describe single-incision trocar-less endoscopic (SITE) technique which simplifies enucleation and management of residual cavity. METHOD: Inclusion criteria for these cases were patients having single uncomplicated giant hydatid cyst >5 cm present at the surface of the liver and palpable on clinical examination. The cysts which were <5 cm, multiple, deep-seated and impalpable were excluded from the study. TECHNIQUE: An incision of 1 cm is marked over the site of the maximum bulge and deepened to open peritoneum, cyst is held with two stay sutures, injection of scolicidal agent and aspiration is done and suction of the cyst content is done. After suction of the contents, 5 mm telescope is inserted, and the cyst cavity is inspected, clearance and cyst procedure is done. RESULTS: In 6 years, 62 cases of giant hydatid cyst fulfilling the inclusion criteria and were taken for SITE technique. SITE was successful in all patients and none needed a conversion. Twenty-nine (46.77%) underwent omentopexy and three (4.83%) underwent SITE capitonnage. There was post-operative biliary leak in one (0.016%) patient who underwent capitonnage, which was managed by prolonged drainage which resolved in 10 days. Mean operative duration was 52 min (30 min to 85 min). Mean follow-up was for 18 months (12–36 months). One (0.016%) patient had cyst recurrence. DISCUSSION: SITE has advantages of endoscopic clearance and does not require special ports which are expensive, technically difficult to use and often unavailable. It allows controlled handling, effective suction and easier management of bile communication. SITE can be a preferred procedure for endoscopic management of giant liver hydatid cysts. CONCLUSION: SITE management of giant liver hydatid cyst seems to be a reliable treatment modality as it is minimally invasive, efficient, easy to perform and effective.